The Effects of Immigration on Wages: An Application of the Structural Skill-Cell Approach - Michael Gerfin; Boris Kaiser (Swiss Journal of Economics and Statistics, 2010)
This paper investigates how recent immigration inflows from 2002 to 2008 have affected wages in Switzerland. This period is of particular interest as it marks the time during which the bilateral agreement with the EU on the free crossborder movement of workers has been effective. Since different types of workers are likely to be unevenly affected by recent immigration inflows, we follow the "structural skill-cell approach" as for example employed by Borjas (2003) and Ottaviano and Peri (2008). This paper provides two main contributions. First, we estimate empirically the elasticities of substitution between different types of workers in Switzerland. Our results suggest that natives and immigrants are imperfect substitutes. Regarding different skill levels, the estimates indicate that workers are imperfect substitutes across broad education groups and across different experience groups. Second, the estimated elasticities of substitution are used to simulate the impact on domestic wages using the actual immigration inflows from 2002 to 2008. For the long run, the simulations produce some notable distributional consequences across different types of workers: While previous immigrants incur wage losses (-1.6%), native workers are not negatively affected on average (+0.4%). In the short run, immigration has a negative macroeconomic effect on the average wage, which, however, gradually dies out in the process of capital adjustment.
Keywords: E24; F22; J61; J31; 330; immigration; wages; labour demand; labour supply; skill groups; elasticity of substitution